The function of omega-3 polyunsaturated fatty acids in response to cadmium exposure - Chen, Zhi; Lu, Qinyue; Wang, Jiacheng; Cao, Xiang; Wang, Kun; Wang, Yuhao; Wu, Yanni; Yang, Zhangping (Frontiers in Immunology, 2022)
Throughout history, pollution has become a part of our daily life with the improvement of life quality and the advancement of industry and heavy industry. In recent years, the adverse effects of heavy metals, such as cadmium (Cd), on human health have been widely discussed, particularly on the immune system. Here, this review summarizes the available evidence on how Cd exposure may affect health. By analyzing the general manifestations of inflammation caused by Cd exposure, we find that the role of omega-3 (n-3) polyunsaturated fatty acids (PUFAs) in vivo can counteract Cd-induced harm. Additionally, we elucidate the effects of n-3 PUFAs on the immune system, and analyze their prophylactic and therapeutic effects on Cd exposure. Overall, this review highlights the role of n-3 PUFAs in the pathological changes induced by Cd exposure. Although n-3 PUFAs remain to be verified whether they can be used as therapeutic agents, as rehabilitation therapy, supplementation with n-3 PUFAs is reliable and effective.